SIGN OF MORSE #2 - Ossi Darma Desprian (SELONDING, 2017)
Sign of Morse # 2 is a creation of ethnic musical composition inspired by the empirical experience of the author, that is overseas trip undertaken from their hometown to the other areas to seek new experiences.Sign of Morse # 2 sourced with three ethnic groups in Indonesia, namelyPadang, Berau and Yogyakarta. The authors add textual idea of using Morse as the cultivation of the material so that the concept more interesting creation.The background of the birth of a creation based on the basic functions and interests as well as the hearts of the composer itself. Social criticism, natural phenomena, even outpouring composer a wide variety of content contained in a creation. Sign of Morse # 2 has a goal to provide a reference musical ideas through Morse and hope to contribute to the community or audience of creation in order to become a lighter to always create. The author hopes that the birth of this creation, Morse could serve as an example for contextual idea of making the work of musical composition.Each symbol is a result of word processing Padang, Berau and Jogja given beats to determine measures of which will be used in every part of the composition. As for the tone processing, the author uses the pentatonic represents Javanese (Pelog), Hijaz represent Berau and Minang represented by imitation and Bansi talempong technique that has been processed into a musical composition.